Accreting Neutron Stars in 3D General-relativistic Magnetohydrodynamic Simulations: Jets, Magnetic Polarity, and the Interchange Slingshot - Kyle Parfrey; Alexander Tchekhovskoy (The Astrophysical Journal, 2024)
Accreting neutron stars differ from black holes by the presence of the star’s own magnetic field, whose interaction with the accretion flow is a central component in understanding these systems’ disk structure, outflows, jets, and spin evolution. It also introduces an additional degree of freedom, as the stellar dipole can have any orientation relative to the inner disk’s magnetic field. We present a suite of 3D general-relativistic magnetohydrodynamic simulations in which we investigate the two extreme polarities, with the dipole field being either parallel or antiparallel to the initial disk field, in both the accreting and propeller states. When the magnetosphere truncates the disk near or beyond the corotation radius, most of the system’s properties, including the relativistic jet power, are independent of the star–disk relative polarity. However, when the disk extends well inside the corotation radius, in the parallel orientation the jet power is suppressed and the inner disk is less dense and more strongly magnetized. We suggest a physical mechanism that may account for this behavior—the interchange slingshot—and discuss its astrophysical implications. When the star is in the rapidly accreting regime, which in most cases will be associated with strong spin-up, we expect large observational differences between the two magnetic orientations. This may be reflected in increased variability as the accretion flow drags in successive magnetic structures of varying polarity.